Influence of cold curing temperature and freeze–thaw on the UCS of stabilised silty sand. Issue 4 (24th November 2021) - Rothhämel, M.; Laue, J.
Abstract : Fine-grained soils are often not suitable as subsoil for roads or railways or other large-scale constructions due to their sensitivity to settlement as well as their frost susceptibility. However, engineering properties and frost durability of such soils can be improved by stabilising them with hydraulic binders. Stabilisation is quite often used in countries with a moderate climate, but seldom in cold climates. This paper presents a laboratory study of a Swedish silty sand stabilised with Multicem, a cement containing 50% cement kiln dust. The unconfined compressive strength (UCS) was used as a measure of strength and different binder contents and different curing times were investigated. The UCS was measured before and after 12 freeze–thaw cycles and after subsequent curing for 28 d. The curing conditions were adapted to conditions in northern countries (+4°C). The results showed that the strength gained by stabilisation is sufficient even at this cold curing temperature. The strength after the freeze–thaw cycles was still significantly higher than that of soil without stabilisation. The recovery time after freeze–thaw cycles may allow continued curing, resulting in higher strength. This remaining strength should be the subject of further investigation.